Determination of 4,4-(propane-2,2-diyl) diphenol (Bisphenol A) Concentration in Canned Tomatoes - G.P Fabusola; V.O.E Akpambang (Journal of Tropical Pharmacy and Chemistry, 2021)
Bisphenol A (BPA) is a chemical used in the production of polycarbonate plastics and for lining metal cans, used in canned foods. BPA is a well-known endocrine disrupting chemical, it therefore, is very hazardous to human health. BPA levels were determined in three brands of canned tomatoes (Gino, Super Mama, Derica) as sold in Nigerian markets. The samples were analyzed using solvent extraction, separation and quantitation by gas chromatography- mass spectrometric method. The recovery value for BPA in the method was 89% with the relative standard deviations of 3%.The BPA concentration in the samples ranged from 0.124 to 0.141 (), which are higher than the European Food Safety Authority Specific Migration Limit (SML) of 0.05 mg/kg in food sample. The samples analyzed in this work may be, therefore, of a potential health concern to the consumers.